Avaliação das reformas recentes no setor elétrico brasileiro e sua relação com o desenvolvimento do mercado livre de energia - Walvis, Alida (2014)
There are many challenges inherent to the functioning of a sector as complex as the electricity sector, in which the results of a given measure may take years until it reaches maturity and only then its impact on the institutional framework gets to be fully known by the policy makers. Taking the electricity sector as a backdrop, this dissertation presents the basis for what would be an ideal reform, usually referred to in the literature as 'textbook reform', followed by a presentation of the regulatory evolution of the Brazilian electricity sector, from 1930 until early 2014, with special emphasis on the reforms that took place during the period of 1995 to 2004. The bibliographic research presented in this dissertation is divided into four chapters and analyzes the present situation of the liberalization of the Brazilian electricity market and suggests feasible improvements in order to develop this market in Brazil.